Lectotype designations and taxonomic corrections on Neotropical Scutelleridae described by G. Breddin (Hemiptera: Heteroptera) - Rédei, Dávid; Tsai, Jing-Fu; Eger, Joseph E., Jr. (Zootaxa, 2016)
Lectotypes are designated and documented for the following species and infrasubspecific taxa: Dystus villosus Breddin, 1904; Lobothyreus breviceps Breddin, 1914; Pachycoris torridus (Scopoli, 1772) var. laetissimus Breddin, 1906 (originally proposed as var. laetissima); P. torridus var. moestissimus Breddin, 1906 (originally proposed as var. moestissima); Polytes speculiger Breddin, 1914. The identities of the taxa in concern are clarified. The following new junior subjective synonyms are proposed: Pachycoris torridus (Scopoli, 1772) = P. torridus var. laetissimus Breddin, 1906, syn. nov., = P. torridus var. moestissimus Breddin, 1906, syn. nov.